A natureza jurídica do ADCT na CF/88 e a atuação do poder reformador no contexto da crise de perenidade das promessas constitucionais - Deocleciano, Pedro Rafael Malveira (2019)
The relationship between time and law is intense and problematic, since normative accommodation presupposes minimally the consonance with a series of intangible extranormative factors, such as politics, economics, and the uses and customs of a given reality. And the norms and institutes of intertemporal law would have the difficult task of regulating the transitional situations between normative systems, for even though this legislative concern exists, complexity calls into question the reductionist attempt to capture, by the creation of generic or specific norms, the reality. Time, as a cultural construction of societies, conditions its other institutions, and with law would be no different. The process of revoking and overcoming the normative factuality of a legal regime looms in terms of complexity when faced with constitutional changes. The advent of a new constitution, of major changes made by the reforming power or even of a significant decision of the constitutional jurisdiction that results in a mutation or its delayed or prospective fulfillment, regarding the temporal effects implies the raising of intertemporality, taking into account account the force that a modification impels to the legal situations until then consolidated. Transitional constitutional norms, within Brazilian constitutionalism, perform a fundamental task of stabilizing institutions and subjective rights in a new legal order, softening the impact of constitutional change as they regulate pending situations, create new institutions, define the political process elective positions and reduce, by reception, the normative void that would compromise the very balance of the current constitution. Having as its premise the constitutional norm condition, the ADCT (Transitional Constitutional Provisions Act) has, however, peculiar purposes, as well as being endowed with the provisionality attribute which, to some extent, contributes to the consolidation of the constitutional project. These essential characteristics, which reveal the exceptional nature of its existence in the constitutional text, are contrasted with a broad process of constitutional reforms that not only extend its validity, but also create situations that differ from the permanent text, distorting its purpose. and thus undermining the normative force of the 1988 Constitution, turning its normativity into mere promises. Thirty years later, the ADCT (Transitional Constitutional Provisions Act), through its reform action, is growing in number of devices and in antagonism in relation to the fundamental processes and objectives of the Federative Republic of Brazil. so relevant and directly affecting the course of Brazilian constitutionalism.